THE EFFECT OF LAND AND BUILDING RIGHTS ACQUISITION DUTY (BPHTB) AND GROUNDWATER TAX ON REGIONAL INCOME OF BANDAR LAMPUNG CITY 2016-2020 - Dewi Situmorang; Amelia Anwar; Astrid Aprica Isabella (Peradaban Journal of Economic and Business, 2022)
The purpose of this study was to determine the effect of land and building rights acquisition fee and Groundwater Tax partially on Regional Original Revenues in 2016-2020 in Bandar Lampung, and also to determine the simultaneous effect of land and building rights acquisition, and Groundwater Taxes on Regional Original Revenues in 2016- 2020 in the city of Bandar Lampung. This research is a descriptive study using target report and tax realization data from BPPRDBandar Lampung in 2016-2020, and data analysis using multiple linear regression.Based on the results of this study it is known that the land and building rights acquistion fees has a significant effect on the PAD of Bandar Lampung in 2016-2020, where these resualt of the t test greater than t table (5,336>2,002). Groundwater tax has no significant effect on the PAD of Bandar Lampung. This can be shown by the significance value 2,821>2,002 and obtained from a significance value of 0,07>0,05. And the results of the f test show the results of the calculated f tes are greater than f table 31,218>3,15. Based on these results, it can be concluded that simultaneous the is a significant effect between BPHTB revenue and groudwater tax on PAD Bandar Lampung for the 2016-2020 period.